The Experience of Using Plain Balloon Percutaneous Venoplasty in Central Vein Stenosis in Hemodialysis Patient; Insight for Future Better Development Strategy - Sawitri Satwikajati; Novi Kurnianingsih (Heart Science Journal, 2023)
Background :Central vein stenosis is a most complication among hemodialysis patient who inserted catheter or access for dialysis. The proper management is still challenging because venoplasty as the main recommendation but it had potential complication. The comparable datas of plain vs drug coated balloon were still exist. In this case presentation we will discuss about the use of plain ballon venoplasty as an urgent strategy to relieved central vein stenosis in hemodialysis patient and it’s outcome after procedure in our hospital. Case :Female, 56 years old came to Saiful Anwar Hospital with unilateral upper extremity edema, she felt heavy to move her arm, a litte bit numbness, and no history of pain on her arm. She had been undergo routine hemodialysis and had history of AV shunt inserted for 3 months ago. She came with compos mentis, GCS 456, BP 160/92 mmHg, HR 68 bpm, RR 20 tpm, SpO2 98% RA, temp 36.4oC, Hb 8.0 mg/dL, Ur 53.6 mg/dL, Cr 5.4 mg/dL, eGFR 1.73. From physical examination we got good peripheral oxygen saturation, we suggested this patient with central vein stenosis. We performed venography resulted stenosis 95% at brachiocephalic vein and undergo plain balloon percutaneous venoplasty. After procedure her right upper extremity was getting better. We observes this patient, but in the next three months after procedure of plain balloon percutaneous venoplasty she complained that her right upper extremity became swollen again. We performed re-venography and resulted with restenosis of brachiocephalic vein. She underwent percutaneous venoplasty again and the evaluation untik now was better, the diameter of upper right extremity became smaller and she can do her daily activity. Conclusion :Central vein stenosis was one of the most complication after dialysis catheter insertion. We performed percutaneous venoplasty and observed the outcome of this patient. After 3 months, the symptom was recurrent and we performed percutaneous venoplasty again. Keywords : Central vein stenosis, venoplasty, plain balloon.